Are we missing a trick by not exploiting fruit flies in inflammation-led drug discovery for neurodegeneration? - Price, R.; Ramirez-Moreno, M.; Cooper, A.; Singh, R.; Ming Khaw, Y.; Mudiwa Mhaka, A.; Sivanantharajah, L.; Mudher, A. (Expert opinion on drug discovery, 2025)
Introduction: Alzheimer's disease (AD) remains a formidable challenge in neurodegeneration research, with limited therapeutic options despite decades of study. While Drosophila melanogaster has been instrumental in in modeling AD related Tau and amyloid beta toxicity, inflammation, a key driver of AD pathology, remains unexplored in fly models. Given the evolutionary conservation of innate immune pathways between flies and mammals, drosophila presents a powerful yet underutilized tool for inflammation led drug discovery in AD. Areas covered: This perspective highlights the relevance of Drosophila in studying neuroinflammatory processes, including microglial-like glial activation, systemic inflammation and gut-brain axis interactions. It further explores how fly models can be leveraged to screen anti-inflammatory compounds and dissect immune related genetic factors implicated in AD. Expert opinion: By integrating immune modulation in Drosophila-based drug discovery pipeline we can accelerate the identification of novel therapeutic strategies. Fully exploiting the potential of Drosophila in inflammation led drug screening may usher in a new era of AD therapeutics, bridging gaps between fundamental research and translational medicine.